European Union development assistance for North Korea (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
This chapter provides an analysis of the development of relations between the European Union and North Korea, with particular emphasis on EU development assistance to the country. It addresses questions regarding the nature of EU development assistance, its alignment with the United Nations Sustainable Development Goals, and EU policy objectives. It also compares EU development assistance with aid provided by other countries and international organizations. Present EU assistance primarily focuses on supporting the agricultural sector, combating poverty, and promoting sustainable agriculture. This assistance aligns with the objectives of EU development policy, which aims to eliminate poverty, support sustainable development, defend human rights, promote gender equality, and protect the environment and climate. By considering multiple aspects, the chapter makes a significant contribution to understanding EU development policy towards North Korea and its potential impact on the situation on the Korean Peninsula.